Mechanical Compression of Human Airway Epithelial Cells Induces Release of Extracellular Vesicles Containing Tenascin C - Chimwemwe Mwase; Thien-Khoi N. Phung; Michael J. O’Sullivan; Jennifer A. Mitchel; Margherita De Marzio; Ayşe Kılıç; Scott T. Weiss; Jeffrey J. Fredberg; Jin-Ah Park (Cells, 2022)
Aberrant remodeling of the asthmatic airway is not well understood but is thought to be attributable in part to mechanical compression of airway epithelial cells. Here, we examine compression-induced expression and secretion of the extracellular matrix protein tenascin C (TNC) from well-differentiated primary human bronchial epithelial (HBE) cells grown in an air–liquid interface culture. We measured TNC mRNA expression using RT-qPCR and secreted TNC protein using Western blotting and ELISA. To determine intracellular signaling pathways, we used specific inhibitors for either ERK or TGF-β receptor, and to assess the release of extracellular vesicles (EVs) we used a commercially available kit and Western blotting. At baseline, secreted TNC protein was significantly higher in asthmatic compared to non-asthmatic cells. In response to mechanical compression, both TNC mRNA expression and secreted TNC protein was significantly increased in both non-asthmatic and asthmatic cells. TNC production depended on both the ERK and TGF-β receptor pathways. Moreover, mechanically compressed HBE cells released EVs that contain TNC. These data reveal a novel mechanism by which mechanical compression, as is caused by bronchospasm, is sufficient to induce the production of ECM protein in the airway and potentially contribute to airway remodeling.